Prevention of contrast-associated acute kidney injury in an era of increasingly complex interventional procedures - Somkereki, Cristina; Palfi, Renata; Scridon, Alina (Frontiers in Medicine, 2024)
Radiological and interventional cardiology procedures are in continuous expansion, leading to an important increase in the incidence of contrast-associated acute kidney injury (CA-AKI). Although numerous methods of CA-AKI prevention have been studied, at present, there is no consensus on the definition of this entity or on its prevention. In this paper, we aim to provide a critical analysis of the existing data on the epidemiology, pathophysiology, and clinical significance of CA-AKI. Existing and emergent approaches for CA-AKI prevention are also discussed, with a focus on parenteral fluid administration and on the most recent clinical and experimental data. We also emphasize a number of questions that remain to be answered, and we identify hotspots for future research.